The speech act realisation of requests and greetings by non-native and native speakers of siSwati : communication challenges faced by American Peace Corps Volunteers in their interaction with Swazi people - Sithebe, Faith Bonsile (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil )--University of Stellenbosch, 2011.